Contributions of Guthi System for the Protection of Heritage - Subedi, Salik Ram (Journal of Advanced College of Engineering and Management, 2022)
The main objective of this article is to illustrate the roles of the Guthi system in Nepalese society. The paper discusses the contribution of Guthi system for the protection of heritage in the Kathmandu Valley. Effects of technological advancement on the ability of the Guthi system to preserve and maintain tangible and intangible cultural heritages of Nepal are yet inalienable aspects of the research. The Guthi system seems to have been focusing on the preservation of the religious, cultural, and social services along with organizing and performing rituals, Jatra, festival, chariot, worshiping deities, promotion, and protection of temples and monasteries. The establishment of the Guthi system was based on the social and cooperative promotion of such cultural and religious aspects. This system has endured a number of centuries the backbone of Nepalese culture and community. Guthi endowments were/are given to religious and charitable institutions. Lands are granted in order to maintain temples, hold religious ceremonies, support the population, and so on.